DESCRIPTION OF ADOLESCENT BEHAVIOUR ABOUT SPERMARITAL SEXUAL AT SMK PGRI CIUMBULEUIT BANDUNG - Andini, Andini H; Efrasianty, Efrasianty N; Handiana, Handiana T (JURNAL KESEHATAN KARTIKA, 2021)
Sexual behavior is a behavior that driven by sexual desire with opposite sex or same sex without legitimate marriage .One of the factor that influence the premarital sexual behavior is gender .The research purpose is to know the adolescent behavior about premarital sexual at SMK PGRI Ciumbuleuit Bandung. The method is descriptive with 50 respondents. The sampling is total sampling. The data was taken by questionnaire data analysis was presented by frequency distribution the result is mostly of adolescent have good behavior (76%), and the others have not good behavior (24%). The boys have good behavior as much as 38% and, the other boys have not good behavior 8%, the girls have good behavior 8%, The girls have good behavior as much as 23 persons (8%). The other girls have not good behaviour as much as 38% The recommendation for the school improve the knowledge and have attention to students to avoid premarital sexual behaviour especially at SMK PGRI Ciumbuleuit Bandung and do counselling about premarital sexual to improve the knowledge as information material for teacher to avoid the premarital sexual in adolescent.